The importance of domestication in the conservation of edible wild fungi in Mexico - Alvarado-Castillo, Gerardo; Mata, Gerardo; Benítez-Badillo, Griselda (Bosque (Valdivia), 2017)
In Latin America, including Mexico, the tremendous degradation of forests has drastically altered the ecological, social and cultural contexts associated with them. Edible wild fungi form part of the eating and subsistence strategy of the local inhabitants and of the biocultural richness. This resource is currently at risk owing to the growing demand for its gastronomic and nutraceutical properties, and because of the lack of knowledge for its sustainable use. All of this increases the probability of overexploiting or driving some species extinct, especially the most traditionally used and well-known ones. Because of this, it is necessary to develop an understanding of the role of edible wild fungi in agroecosystems, and to develop technologies that allow them to be produced under domestication. This review examines the theoretical and conceptual background of the challenges of managing fungi and the implications of their domestication; emphasizing the need to take into account ethnomycological knowledge and use an interdisciplinary approach that favors a balance between conservation and development. The proper management of this resource could contribute to local economies and even become a driver of social transformation for rural and indigenous communities in the forests of Mexico.